An integrated approach using ozone nanobubble and cyclodextrin inclusion complexation to enhance the removal of micropollutants - Fan, Wei; An, Wengang; Huo, Mingxin; Xiao, Dan; Lyu, Tao; Cui, Jingyu (Elsevier, 2021)
Ozone (O3) has been widely used for the elimination of recalcitrant micropollutants in aqueous environments, due to its strong oxidation ability. However, the utilization efficiency of O3 is constrained by its low solubility and short half-life during the treatment process. Herein, an integrated approach, using nanobubble technology and micro-environmental chemistry within cyclodextrin inclusion cavities, was studied in order to enhance the reactivity of ozonisation. Compared with traditional macrobubble aeration with O3 in water, nanobubble aeration achieved 1.7 times higher solubility of O3, and increased the mass transfer coefficient 4.7 times. Moreover, the addition of hydroxypropyl-β-cyclodextrin (HPβCD) further increased the stability of O3 through formation of an inclusion complex in its molecule-specific cavity. At a HPβCD:O3 molar ratio of 10:1, the lifespan of O3 reached 18 times longer than in a HPβCD-free O3 solution. Such approach accelerated the removal efficiency of the model micropollutant, 4-chlorophenol by 6.9 times, compared with conventional macrobubble ozonation. Examination of the HPβCD inclusion complex by UV-visible spectroscopy and Nuclear Magnetic Resonance analyses revealed that both O3 and 4-chlorophenol entered the HPβCD cavity, and Benesi-Hildebrand plots indicated a 1:1 stoichiometry of the host and guest compounds. Additionally, molecular docking simulations were conducted in order to confirm the formation of a ternary complex of HPβCD:4-chlorophenol:O3 and to determine the optimal inclusion mode. With these results, our study highlights the viability of the proposed integrated approach to enhance the ozonation of organic micropollutants
Keywords: inclusion complex; HPβCD; emerging organic contaminants; chlorophenol; advanced oxidation